Brain parenchyma penetration by intrathecal nonionic iopamidol. - Sage, M R; Wilcox, J (American Journal of Neuroradiology, 1983)
Iopamidol, a nonionic, water-soluble contrast medium, has been recently recommended for myelography. As with other such media, the extent of parenchymal penetration is of interest in relation to the genesis of clinical complications. In this study the degree and depth of brain penetration of intrathecal iopamidol, using an iodine concentration of 280 mg l/ml, were compared at 15 and 60 min in adult greyhound dogs using coronal computed tomographic scanning of the brain after removal. A significant but patchy penetration corresponding to the cortical sulci was demonstrated at 15 min, while by 60 min there had been a further increase in the distribution and concentration of the contrast medium. Comparing the present study with a previous series using metrizamide and methylglucamine iothalamate at a similar iodine concentration (280 mg l/ml), no significant difference in the depth or degree of penetration at 60 min was found between the three contrast media, indicating a similar rate of diffusion across the cerebrospinal fluid/brain interface. Therefore, any difference in neurotoxicity is not explained by a reduced concentration of contrast medium due to variation in the rate of diffusion across this interface.